Artificial Intelligence Education and Training Based on Machine Learning and Computer Vision to Improve Technological Literacy of Bina Satria Vocational School Students in Medan City - Wahyu Saptha Negoro; Ratih Adinda Destari; Asbon Hendra Azhar; Fhery Agustin; Achmad Syahrian (Majalah Ilmiah UPI YPTK, 2026)
The development of Artificial Intelligence (AI) technology has had a significant impact on various sectors, including education. However, the level of technological literacy, particularly related to Machine Learning and Computer Vision, among students is still relatively low, so educational efforts are needed to improve students' understanding and skills in these technologies. This community service activity aims to improve the technological literacy of SMK Bina Satria Medan City students through practice-based education and training on the basic concepts of Artificial Intelligence, Machine Learning applications, and the implementation of Computer Vision using easily accessible software. The implementation method of this activity includes the stages of needs identification, material preparation, socialization, demonstration, direct practice using Google Colab, and evaluation through pre-tests and post-tests. The training materials include an introduction to Artificial Intelligence, types of Machine Learning, digital image processing, image classification using Convolutional Neural Networks (CNN), and a simple implementation of Computer Vision for object recognition. The results of the activity showed an increase in participants' knowledge and understanding of Artificial Intelligence concepts, as indicated by an increase in evaluation scores after the training. In addition, participants were able to independently implement a simple model for image classification using the Google Colab environment. This activity positively contributes to improving students' digital competencies while preparing them for technological advancements in the Industrial Revolution 4.0 and Society 5.0. It is hoped that similar activities can be implemented sustainably with broader coverage to support human resource development in the information technology sector.